Connect with experts and get insightful answers on IDNLearn.com. Join our Q&A platform to get accurate and thorough answers to all your pressing questions.
Step-by-step explanation:
that this is an arithmetic sequence of terms, where every term is created by adding (or subtracting) to/ from the previous term.
a1 is the starting value = 12
then
a2 = a1 - 8 = 12 - 8 = 4
a3 = a2 - 8 = a1 - 8 - 8 = -4
every term is 8 less than the previous term.
so, we see, we can express the nth term of the sequence also in terms of a1 :
an = an-1 - 8 = a1 + -8×(n-1) = a1 - 8×(n-1)